Ultrafast Laser‐Shock‐Induced Confined Metaphase Transformation for Direct Writing of Black Phosphorus Thin Films. Issue 10 (16th January 2018) - Qiu, Gang; Nian, Qiong; Motlag, Maithilee; Jin, Shengyu; Deng, Biwei; Deng, Yexin; Charnas, Adam R.; Ye, Peide D.; Cheng, Gary J.
Abstract: Few‐layer black phosphorus (BP) has emerged as one of the most promising candidates for post‐silicon electronic materials due to its outstanding electrical and optical properties. However, lack of large‐scale BP thin films is still a major roadblock to further applications. The most widely used methods for obtaining BP thin films are mechanical exfoliation and liquid exfoliation. Herein, a method of directly synthesizing continuous BP thin films with the capability of patterning arbitrary shapes by employing ultrafast laser writing with confinement is reported. The physical mechanism of confined laser metaphase transformation is understood by molecular dynamics simulation. Ultrafast laser ablation of BP layer under confinement can induce transient nonequilibrium high‐temperature and high‐pressure conditions for a few picoseconds. Under optimized laser intensity, this process induces a metaphase transformation to form a crystalline BP thin film on the substrate. Raman spectroscopy, atomic force microscopy, and transmission electron microscopy techniques are utilized to characterize the morphology of the resulting BP thin films. Field‐effect transistors are fabricated on the BP films to study their electrical properties. This unique approach offers a general methodology to mass produce large‐scale patterned BP films with a one‐step manufacturing process that has the potential to be applied to other 2D materials. Abstract : A method of directly synthesizing continuous black phosphorus (BP) thin films with arbitrary patterned shapes by employing ultrafast laser writing with confinement is reported. Ultrafast laser ablation of a BP layer under confinement can generate transient nonequilibrium high‐temperature and high‐pressure conditions for a few picoseconds, which induce a metaphase transformation to form a crystalline BP thin film on the substrate.